A segurança do paciente na rede de atenção psicossocial através do cuidado da equipe multiprofissional - Herman, Adriana (2023)
Introduction: Patient safety is a fundamental concern at all levels of healthcare. Therefore, elucidating the risks and factors related to patient safety incidents is of paramount importance to support the development of specific policies and protocols for the safe care of this population. Objective: To characterize studies addressing incidents involving patients in Psychosocial Care and healthcare professionals' safety attitudes, and to assess the association between incidents occurring with patients and safety attitudes of the multidisciplinary team professionals comprising the Psychosocial Care Network (PCN) in the city of Lins, São Paulo. Methodology: This dissertation included two studies. The first is an integrative literature review using the LILACS, MedLine, SciELO, and PubMed databases. National articles in English, Spanish, and Portuguese published between January 2012 and November 2022 were selected. The second study is a cross-sectional study conducted with professionals working in the PCN in the city of Lins, São Paulo, based on the administration of questionnaires for collecting sociodemographic data, incidents in the PCN, and Safety Attitudes (Safety Attitudes Questionnaire - SAQ). Logistic regression models were used to predict the odds ratio for categories of incidents occurring with patients in the PCN and the domains of safety attitudes of the professionals. Results: The integrative review showed that the risk and incidents themselves occurred in all sectors, regardless of the level of healthcare. Factors such as physical infrastructure, team experience, medication administration errors, patient aggression, lack of professional preparedness, and organizational issues were related to incident occurrences. In the cross-sectional study, it was found that safety attitudes such as "job satisfaction" and "teamwork climate" contribute to the patient safety culture in the PCN. Professionals who did not perform hand hygiene showed a higher recognition of stress. Furthermore, those with better communication demonstrated a safer climate and higher job satisfaction, and those who had no knowledge of medication errors showed a safer climate. Conclusion: Incident occurrences were observed at all levels of psychosocial care. Difficulties were found among professionals in distinguishing basic concepts (such as error and risk), limited knowledge of legislation related to patient safety, as well as the practice of safety actions in a partial, compartmentalized, and non-systematic manner. Further studies are necessary to better assess the relationship between the safety culture and the occurrence of adverse events involving patients and professionals working within the psychosocial care network. Additionally, it is suggested that this evaluation be conducted in other areas of the public healthcare system, aiming to improve the quality of care